Mainstreaming disaster risk management for finance: application of real options method for disaster risk sensitive project (2016)
This paper discusses the application of real options analysis for a project that is in the process of construction and was affected by a natural disaster. The use of the analytical method has become a way of thinking in making decisions that should be taught to business school students. The case in this paper is based on an MBA thesis at the University of Gadjah Mada that was intended as a showcase for application of real options to address real business problems. It shows one of the strategies in mainstreaming disaster risk management in the business school that also answers the needs of businesses in the disaster-prone country.